Mozambique - Municipal Development in Mozambique : Lessons from the First Decade - Synthesis Report - World Bank (World Bank, 2012)
Municipalities in Mozambique were established by law in 1997 and elected in 1998 for the first time, only a few years after the peace agreement. Most inherited archaic and dysfunctional remnants of colonial and central government systems and infrastructure, and as such limited progress was achieved in transforming them into functioning local governments during the first mandate (1998-2002). During the second mandate (2003-2008), however, significant improvements were seen as municipalities began to grasp the nettle of local governance and some service delivery challenges. By the end of their first decade most municipalities have reorganized themselves to some extent and a number have undertaken initiatives that are beginning to bear fruit. There remains a long way to go, however, before municipalities will be robust enough to deliver quality local services to meet growing demand. There is a danger that the pace of municipal technical and financial capacity development will be overtaken by the growing municipal population and by transfers of additional mandates. Municipalities, central government, and the Association of Municipalities (ANAMM) need to support municipalities to perform their potentially significant role in improving living conditions, stimulating growth and cementing meaningful democracy in Mozambique. This study provides the first integrated assessment of the challenges of local development and service delivery through a municipal lens. It diagnoses the underlying systemic constraints facing municipalities, discusses some of the specific service delivery challenges of the municipalities, and it sets out recommendations for both central and municipal governments to tackle some of these constraints within an integrated and systemic framework.